A scorecard of progress towards measles elimination in 15 west African countries, 2001–19: a retrospective, multicountry analysis of national immunisation coverage and surveillance data. Issue 3 (March 2021) - Wariri, Oghenebrume; Nkereuwem, Esin; Erondu, Ngozi A; Edem, Bassey; Nkereuwem, Oluwatosin O; Idoko, Olubukola T; Agogo, Emmanuel; Enegela, Joseph E; Sesay, Tom; Conde, Iya Saidou; Kaucley, Landry; Awuah, Anthony Afum-Adjei; et al.
Summary: Background: The WHO Regional Office for the Africa Regional Immunization Technical Advisory Group, in 2011, adopted the measles control and elimination goals for all countries of the African region to achieve in 2015 and 2020 respectively. Our aim was to track the current status of progress towards measles control and elimination milestones across 15 west African countries between 2001 and 2019. Methods: We did a retrospective multicountry series analysis of national immunisation coverage and case surveillance data from Jan 1, 2001, to Dec 31, 2019. Our analysis focused on the 15 west African countries that constitute the Economic Community of West African States. We tracked progress in the coverage of measles-containing vaccines (MCVs), measles supplementary immunisation activities, and measles incidence rates. We developed a country-level measles summary scorecard using eight indicators to track progress towards measles elimination as of the end of 2019. The summary indicators were tracked against measles control and elimination milestones. Findings: The weighted average regional first-dose MCV coverage in 2019 was 66% compared with 45% in 2001. 73% (11 of 15) of the west African countries had introduced second-dose MCV as of December, 2019. An estimated 4 588 040 children (aged 12–23 months) did not receive first-dose MCV in 2019, the majority (71%) of whom lived in Nigeria. Based on the scorecard, 12 (80%) countries are off-track to achieving measles elimination milestones; however, Cape Verde, The Gambia, and Ghana have made substantial progress. Interpretation: Measles will continue to be endemic in west Africa after 2020. The regional measles incidence rate in 2019 was 33 times the 2020 elimination target of less than 1 case per million population. However, some hope exists as countries can look at the efforts made by Cape Verde, The Gambia, and Ghana and learn from them. Funding: None.